Interview with Jon Ericson, October 24, 1970 (Mustang Radio Network, 1970)
[00:00:00] Mustang Radio Network provides non-athletic aspects of campus programs, this one being the reorganization of the college into 7 schools [00:00:48] Interviewer introduces John Ericson, Dean of School of Communicative Arts and Humanities [00:01:20] Ericson details the departments within the new school of Communicative Arts and Humanities [00:02:00] Ericson talks about how the seemingly diverse departments have more in common than appears [00:02:35] Ericson discusses the relationship between humanities and polytechnic programs [00:03:26] Ericson talks about the need for Human values in technical fields [00:04:15] Ericson discusses the objective of the school, to be excellent in the field of humanities [00:05:55] Ericson talks about the service functions of each program in the school [00:06:40] Interviewer begins to finish interview